Implementation of Tahsin and Tahfidz in Implementing Religious Character in Madrasah Ibtidaiyah Al Khoiriyyah 02 Semarang - Fakiroh, Lutfiatul; Zulaikhah, Zulaikhah (Indonesian Journal of Elementary Education (IJEE), 2025)
This study aims to describe the implementation of the tahsin and tahfidz program in shaping the religious character of students at Madrasah Ibtidaiyah Al Khoiriyyah 02 Semarang. The background of this study is the importance of religious character education in an Islamic-based elementary school environment, where the habit of reading and memorizing the Qur'an is believed to be able to instill religious values effectively. The research method used is qualitative with a case study approach. Data were collected through participatory observation, interviews with teachers, and analysis of documentation of tahsin and tahfidz activities. The results of the study indicate that the tahsin and tahfidz program at MI Al Khoiriyyah 02 Semarang is implemented systematically through daily habits such as dhuha prayer, tadarus, and joint prayer before lessons. Teachers act as role models in shaping students' religious character through exemplary behavior, habits, and strengthening religious values. This program has been proven to not only improve the ability to read and memorize the Qur'an, but also foster discipline, honesty, politeness, and motivation to worship in students. In conclusion, the implementation of tahsin and tahfidz consistently can form a strong religious character in madrasah studentsKeywords:Tahsin, Tahfidz, Religious Character, Madrasah Ibtidaiyah,